Avaliação da aderência de práticas de armazenagem de resinas termoplásticas aos princípios da mentalidade enxuta - Silva, Brian (Universidade do Vale do Rio do Sinos, 2008)
The present study analyses storage practices in the petrochemical sector from the point of view of Lean Thinking, taking into consideration the pressing importance of costs, the high volume of production and high volume of inventory intrinsic to the process. The main objective of the study is to present the level adherence that the operations of thermoplastic resin storage have to the principles of the Lean Thinking. The evaluation process developed was broken down into five different sections, one for each of the Lean Thinking principles. Each section had the support by a specialist in the specific field. Following that, the process was applied to professionals of the different areas in three warehouses of the Petrochemical Region of Triunfo/RS, from where it was possible to derive the level of adherence so mentioned, and the existing gaps. Finally, the gaps were jointly analyzed, and operational alternatives to fulfill them in order to better improve the adherence of the entire process to the principles
Keywords: função armazenagem; logística enxuta; mentalidade enxuta; lean logistics; storage function; lean thinking; Engenharias